2023
DOI: 10.2147/prbm.s421165
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness Trajectories, Associated Factors and Subsequent Health in Children and Young People During the COVID-19 Pandemic: A National Matched Cohort Study

Verena Schneider,
Tom Norris,
Manjula Nugawela
et al.

Abstract: Purpose Loneliness is common amongst children and young people (CYP) and is an independent risk factor for poor health. This study aimed to i) determine whether subgroups of CYP with different loneliness trajectories (during the second year of the pandemic) exist; ii) examine associations with socio-demographic characteristics and subsequent health; and iii) understand whether associations between loneliness and subsequent health were modified by SARS-CoV-2 infection. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Traditional methods of bullying (e.g., social exclusion) were more frequently reported than cyberbullying and cyberbullying was lower than expected considering prior research and the profile of our cohort [ 52 , 53 ], in particular the high levels of digital technology usage. Mean baseline scores on the Three-Item Loneliness Scale were higher than reports from general population data [ 54 ], but correspond to other clinical population studies, suggesting it may relate to impairment in social functioning that can be symptomatic of some mental health conditions [ 55 ]. Loneliness may also be exacerbated by excessive time spent online, that would be otherwise spent investing in offline social networks [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 64%
“…Traditional methods of bullying (e.g., social exclusion) were more frequently reported than cyberbullying and cyberbullying was lower than expected considering prior research and the profile of our cohort [ 52 , 53 ], in particular the high levels of digital technology usage. Mean baseline scores on the Three-Item Loneliness Scale were higher than reports from general population data [ 54 ], but correspond to other clinical population studies, suggesting it may relate to impairment in social functioning that can be symptomatic of some mental health conditions [ 55 ]. Loneliness may also be exacerbated by excessive time spent online, that would be otherwise spent investing in offline social networks [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 64%
“… 11 One further study shows that during the pandemic, females, older adolescents and those from deprived areas were at higher risk of loneliness. 13 CLoCk data have also shown that there has been a small decline in mental health among participating CYP during the pandemic, with females and older adolescents having a higher risk of deterioration. 29 In initial CLoCk study publications, test-positive CYP were compared with laboratory-confirmed SARS-CoV-2 test-negative CYP 6 , 7 , 9 , 10 , 12 [and we excluded CYP who had been (re-)infected after their baseline PCR-test].…”
Section: Data Resource Usementioning
confidence: 99%